The Effectiveness of the e-Student Worksheets to Improve Students' Learning Outcomes and Critical Thinking Skills on Digestive System Concepts - Rida Oktorida Khastini; Wineng Siti Rohmah; Aulia Nur Sahida (International Journal of Biology Education Towards Sustainable Development, 2023)
The 21st-century education focuses on emphasizing the use of technology and information. Nevertheless, only some media can support interactive learning. Therefore it causes low student learning outcomes due to a lack of interest in participating in learning. The e-student worksheets are the innovations expected to attract students to be more active during learning. This study aimed to determine the effectiveness of using the e-student worksheets to improve learning outcomes and critical thinking skills as measured by the Kolmogorov-Smirnov method using pre-test and posttest data collection techniques. The study's results stated that the experimental class's posttest average value was 77.2 while that of the control class was 64.4. So the average value of the experimental class is higher than the control class. Based on statistical analysis, proving the results of the significance of the independent sample t-test, namely 0.00 0.05, it can be concluded that using the e-student worksheets effectively improves learning outcomes and students' critical thinking skills.